A sectorial analysis of the gender wage gap along the wage distribution in Spain - Marfil-Cotilla, Marina; Campos-Soria, Juan Antonio; García-Pozo, Alejandro (My University, 2022)
This paper contributes to the study of the gender wage gap in the Spanish service sector along the wage distribution. This analysis of the gender wage gap is carried out in three stages. The first is based on a specific analysis of wages at the sectoral level, disentangling the service sector in hospitality industry, travel agency services, transport industry, and other complementary services. The decomposition of the gender wage gap into its non-discriminatory and discriminatory components for each sector is carried out in the second stage. The third stage consists of the application of an Unconditional Quantile Regression (UQR) methodology to analyse the different determinants of the discriminatory and non-discriminatory components across the wage distribution. The main findings are as follows. There are marked differences in the determinants of the non-discriminatory and discriminatory components of the gender wage gap between sectors. Among the main determinants, the human capital of workers, especially education and educational mismatch, and vertical gender segregation stand out. Regarding the non-discriminatory component, there is an over-representation of men in the highest paid jobs, except in the case of the transport industry. Regarding the discriminatory component, the existence of a lower degree of wage discrimination in the hospitality industry compared to other services is shown. There is a wage penalty for the promotion of women, especially in the transport and travel agency industries. In the hospitality industry, although women are under-represented in the higher-paid jobs, those who do make it to the top are paid more than men.
Keywords: Salarios; Igualdad de género; Gender wage gap; Discrimination; Unconditional quantile regressions; Hospitality; Services